Letter (copy) : Harrow Trades Council - Feather, Victor
035-0105-001 Organisation VF/JH/339 20th November, 1942. REGISTERED POST Miss Alma Seer, Harrow Trades Council, 184a Kenton Road, Kenton, Middx. Dear Miss Seer, HARROW TRADES COUNCIL I am returning herewith the 10 copies of minutes of your Trades Council which you were good enough to leave with me. They have been very helpful, and there are several matters contained in them to which I propose to make reference at the meeting next Thursday. Your communication of November 14th on the subject of the International Brigade has also been passed to me so that I may deal with the whole of this matter when I meet your Council. Yours sincerely, Acting Secretary, T.C.J.C.C. minutes 292/946/35/105